Fall Meeting of the Society of Petroleum Engineers of AIME 1974
DOI: 10.2118/4993-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Underground Coal Gasification Experiment, Hanna, Wyoming

Abstract: In the fall of 1972, the Bureau of Mines began an experiment to investigate the technologic, economic, and environmental considerations of underground gasification of a western subbituminous coal. The gasification site is near the town of Hanna, Wyoming, approximately 70 miles northwest of Laramie. The test results indicate that gas volumes and gas heating values have fluctuated over a wide range depending on operating conditions. The ranges have been from 50,000 to over three million standard cubic feet per d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…2), the relative error range for the main gas single compounds ranges between 4.32 and 9.95% [53], overall indicating quite good agreement, keeping in mind that this is only a snapshot of a reported average gas composition. Alongside, the relative error for the synthesis gas LHV comparison was found to be relatively low (6.60%) [55], probably slightly overestimated as a result of the higher tar and H 2 production prognosis.…”
Section: Case Study Hanna I Vs Model Simulationmentioning
confidence: 54%
See 3 more Smart Citations
“…2), the relative error range for the main gas single compounds ranges between 4.32 and 9.95% [53], overall indicating quite good agreement, keeping in mind that this is only a snapshot of a reported average gas composition. Alongside, the relative error for the synthesis gas LHV comparison was found to be relatively low (6.60%) [55], probably slightly overestimated as a result of the higher tar and H 2 production prognosis.…”
Section: Case Study Hanna I Vs Model Simulationmentioning
confidence: 54%
“…Figs. 2 and 3 compare the dry synthesis gas composition, its lower heating value, and total tar production regarding the main source process of pyrolysis and expected mixed synthesis gas yields [26,47,[53][54][55]. In context of the syngas heating value analysis here, we used the standard internal Aspen Plus® software subroutine (Refsys correlation manager, LHV-0).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over a 4 mo period, an average yield of 1 170 kcal/m3 was produced from a two-hole (inlet/outlet) system. The linked vertical well method was used, and forward burning was found unworkable without prior backward buming (Schrider and Pasini, 1973;Schrider et al, 1974;Campbell et al, 1974). Later analysis of this first test has shown that the linkage path was not performed at the bottom of the seam, which in turn gave the inconsistent product gas composition.…”
Section: Laramie Energy Research Centermentioning
confidence: 99%